2006
DOI: 10.1002/bjs.5276
|View full text |Cite
|
Sign up to set email alerts
|

Meta-analysis of observational studies of ileorectal versus ileal pouch–anal anastomosis for familial adenomatous polyposis

Abstract: Ileal pouch and ileorectal anastomoses have individual merits. Further research is needed to determine which most benefits patients with FAP.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
122
0
3

Year Published

2006
2006
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 174 publications
(128 citation statements)
references
References 44 publications
3
122
0
3
Order By: Relevance
“…Moreover, the number of self-reported symptoms was the strongest predictor of patients' physical and mental health. As expected, symptoms such as diarrhea, nighttime urge of defecation, and flatus, which were previously reported in patients with FAP after prophylactic colorectal surgery, 3 were frequently reported by patients in the current study. However, symptoms not previously reported, such as borborygmi, abdominal distension, abdominal discomfort or pain relieved by defecation, and belching, were reported by 30% to 62% of our patients.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Moreover, the number of self-reported symptoms was the strongest predictor of patients' physical and mental health. As expected, symptoms such as diarrhea, nighttime urge of defecation, and flatus, which were previously reported in patients with FAP after prophylactic colorectal surgery, 3 were frequently reported by patients in the current study. However, symptoms not previously reported, such as borborygmi, abdominal distension, abdominal discomfort or pain relieved by defecation, and belching, were reported by 30% to 62% of our patients.…”
Section: Discussionsupporting
confidence: 90%
“…1,2 Patients with FAP are normally asymptomatic before surgery, but after surgery they report various symptoms, such as an increase in number of bowel movements per day, nighttime defecation, leakage, fecal urgency, difficulty in distinguishing gas from feces, perianal skin problems, and small-bowel obstruction. Most patients also report a need for dietary restrictions 3,4 to avoid disturbing abdominal symptoms. 5 Symptoms have been suggested to be more prevalent in patients with an IPAA than in those with an IRA; 3 knowledge is limited regarding symptoms experienced by patients with an ileostomy.…”
Section: Introductionmentioning
confidence: 99%
“…In an interesting metanalysis, AZIZ et al (2) compared 12 studies published from 1991 to 2003, reuniting 1,002 patients. The authors found less evacuatory dysfunction after IRA and a greater reoperation rate after RPC (23.4% vs 11.6%).…”
Section: Discussionmentioning
confidence: 99%
“…Since its introduction, RPC has suffered continuous modifications in order to achieve better functional outcome, less morbidity and mucosal disease control. Despite some controversies, RPC progressively turned out to be the gold standard treatment for FAP and ulcerative colitis (2) .…”
Section: Introductionmentioning
confidence: 99%
“…Surgical options include subtotal colectomy with ileorectal anastomosis (IRA), total proctocolectomy with ileostomy, and proctocolectomy with or without mucosectomy and ileal pouch anal anastomosis (IPAA) [75][76][77].…”
Section: Management Of the Fap Patientmentioning
confidence: 99%